Takhrij of Hadiths on Tawazun: Core Values in Islamic Education from the Madrasah Textbook - Anadita Veria Sandi; Romlah Abubakar Askar; Abdul Ghofur (UIN Kiai Haji Achmad Siddiq Jember, 2025)
Tawāzun, or balance, is a core principle in Islamic education, emphasizing equilibrium between worldly and afterlife pursuits. In the Qur’an Hadith textbook for Grade VIII Madrasah Tsanawiyah, published by Indonesia’s Ministry of Religious Affairs (2020), two hadiths on tawāzun serve as foundational tools for fostering students' balanced spiritual and social character. This study conducts takhrīj on these hadiths using a library research approach and sanad-matn analysis to trace their origins, authenticity, and embedded Islamic educational values. Findings reveal that both hadiths originate from authoritative sources in the kutub al-tis‘ah, particularly Ṣaḥīḥ Muslim and Sunan al-Nasā’ī. The first hadith (the Prophet’s supplication for the rectification of religion, worldly life, and the hereafter), narrated from Abū Hurairah, has a continuous (muttaṣil) sanad with all thiqah narrators, rendering it ṣaḥīḥ li-dhātihi. The second hadith (the parable of the world likened to water on a finger dipped in the sea), narrated from Mustawrid, is transmitted through five reinforcing chains, also deemed ṣaḥīḥ despite minor non-impactful textual variants. The hadiths convey key Islamic educational values, including moderation, responsibility, physical-spiritual harmony, and holistic awareness of life’s purpose. They are highly relevant for Islamic character education in madrasahs, fostering balanced, optimistic, and hereafter-oriented attitudes amid contemporary challenges of modernization and hedonism. This research fills a gap in takhrīj studies on madrasah textbooks and strengthens the validity of Islamic religious education materials in Indonesia.